Globalization, Food Quality and Labor: The Case of Grape Production in North-Eastern Brazil - Bonanno, Alessandro; Salete Barbosa Cavalcanti, Josefa (The International Journal of Sociology of Agriculture and Food, 2012)
This article investigates the consequences of the production of table grapes for export to corporate supermarkets in the global North on labor in a region of the Brazilian North-east. This production is destined to meet the growing demand for year-round food marketed as quality food. Quality food is required by supermarket chains to increase competitiveness and is guaranteed through third-party certification programs. Despite claims that certification not only maintains product quality but also safeguards the use of labor, the study demonstrates that the global production of quality grapes engenders negative consequences for workers. Laborers work longer for less pay, perform more sophisticated tasks, are employed mostly through temporary contracts, and experience new and more advanced forms of control. Additionally, the article illustrates the ways in which other salient actors, such as global food retailers, brokers and firms, operate in regard to labor and quality grape production. It is concluded that, despite various claims about the objectives of certification programs, the actual use of the certification processes at the local level does not translate immediately into better labor relations in the global South.